Utilization of Booklet Media in Providing Information Services for Students' Understanding of Career Choice - Suriatie, Mimi; Rizka, Ramadhanti; Sangalang, Oktamia Karuniaty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This study is an experimental research using the